Fan Labour in Closed Online Spaces: Admin Practices and Dynamics in the Enhypen WhatsApp Fandom - Vina Raihani; Novi Kurnia (Universitas Ahmad Dahlan, 2025)
Advancements in media technology have enabled K-pop fans to form active online communities where they express loyalty through fan labour by creating content, organizing projects, and investing personal resources to support their idols. This study explores how WhatsApp community admins perform fan labour and sustain participation within a closed digital environment. Active K-pop fandoms that produce and share fan-made content have evolved into digital communities where fans voluntarily contribute to both idols and entertainment agencies. Using a netnographic method, this study involved four months of participatory observation in the WhatsApp community Engene Team ID (September–December 2024). Data were collected through group interactions, observations, and interviews with six active members, including admins and regular members. Results show that admins play key facilitative roles by managing information flow, coordinating fan projects, and connecting internal members with broader fandom activities through a structured system of recruitment, task division, and collaboration. While these practices are often framed as hobbies or leisure pursuits, they also reflect unpaid digital work characterized by emotional and temporal strain and a desire for non-material recognition. By extending Jenkins’ participatory culture theory and applying Fuchs’ concept of digital work to closed social media spaces, this study demonstrates how collaborative fan labour creates structured roles and shared responsibilities that sustain the fandom ecosystem and blur the boundaries between leisure and labour. Future studies could examine how gendered expectations and exploitation influence leadership and recognition in fandom communities.